A novel framework for water right conflict resolution considering actors' power and inter-organizational relationships analysis. Issue 3 (16th March 2022) - Zanjanian, Hossein; Niksokhan, Mohammad Hossein; Ghorbani, Mehdi; Rezaei, Abdul Razaq
Abstract: Water allocation from reservoirs has always been a challenging issue for decision-makers. The more the stakeholders in the allocation projects, the more conflicts among them could be expected to receive more water rights. As a result, it is necessary to study the relations and power among organizations. In this study, the Ilam dam was used as the case study, and the social network analysis was also used to assess the interactions among the involved organizations and evaluate their power using centrality measures. Based on the network analysis and actors' power assessment, a novel approach was applied to define and analyze the conflict associated with water quantity allocation. Accordingly, the Graph Model for Conflict Resolution was used for both basic and power-asymmetric conflict analysis models. In the power-asymmetric approach, the direct power scenario gives the most powerful actor the possibility of punishing the violating organizations using their political and executive power. Based on the status quo of the conflict, the results obtained from the equilibrium analysis show that both the power of the main actor and the nature of relationships other actors have with the most powerful actor directly influence the conflict's outcome. HIGHLIGHTS: Building the model of inter-organizational network related to water allocation. Application of social network analysis to assess actors' power. Analysis of collaborative and conflictive relationships to visualize the conflict. Applying game theory to analyze the basic and power-asymmetric conflict models. A novel method to study the effect of actors' relationships on the equilibrium results. Graphical Abstract